Pemanfaatan Digital Marketing untuk Memperluas Strategi Pemasaran Produk Furniture dari Bahan Kayu Rubber - Januar Al Amien; Hammam Zaki; Eka Pandu Cynthia; Ismanto, Edi (Jurnal Pengabdian UntukMu NegeRI, 2024)
The COVID-19 pandemic, which has affected Indonesia for the past three years, has had a significant negative impact on a number of industries, including the Micro, Medium, and Small Enterprises (MSME) sector, which has been particularly hard hit. Pekanbaru City has 105,445 MSMEs, with data indicating that there are as many as 1,034 MSMEs, which produce a range of goods used by the community, including furniture products and various wood-based office and home furnishings. Of course, if development is carried out for MSME wood craftsmen, this is a potential aspect for the City of Pekanbaru. UMKM Furniqa Woodcraft as a raw material to create furniture items like chairs, tables, cabinets, and various other handicraft products uses rubber wood. However, there has been a significant drop in sales since the Covid-19 pandemic, so a solution must be found. In an effort to increase product marketing, service activities performed include training and assisting with managing Digital Marketing. This activity is implemented using a variety of approaches, including the Interview and Discussion Method, the Training Method, and the Evaluation Method. The evaluation of the implementation of digital marketing training and mentoring showed that employees at Furniqa Woodcraft had increased knowledge competence by 75.875%.